Innovating in practice: How to shape (startup) ecosystems - Mele, Cristina (My University, 2019)
How to build startup Ecosystem. A Service Dominant Logic Approach. There is a growing interest in the process by which universities proceed to obtain value from research and transfer technology (Galán-Muros et al., 2017; Muschio et al. 2016; Perkman et al. 2013; Baldini, 2010; Gomez Gras et al., 2008: Lockett and Wright, 2005). This process is usually linked to innovation; generally, the strategy involves the organization developing institutions (rules) that encourage scholars and other university staff to achieve sufficient benefits to become involved in the process, in which both academics and graduates benefit from the results (i.e., through the creation of job opportunities), as proposed by Rizzo (2015) and Friedman and Silberman (2003). Scandura (2016, p.1907) highlights the relevance of the University in this process: “The exchange of knowledge between academia and industry is therefore an essential mechanism to bring science to the market and foster innovation and economic growth”. The last report on Science, Research and Innovation Performance of the EU (2018, pp.4) the European Commissioner for Research, Science and Innovation posits “Europe currently benefits from distinctive strengths, but also faces weaknesses that we need to address. Europe is the world´s largest producer of high quality scientific knowledge, and yet its innovation performance remains far below its potential. EU invests around 20% of its GDP in R&D, while the United Stated, Japan and South Korea invest 2,8%, 3,3% and 4,2% respectively (…) Europe generates many exciting start-ups but has been largely left behind in the development of major new digital platforms, and lacks those transformational entrepreneurs that have disrupted entire industries at a global scale”. The present conference is related to to find out how to improve the innovation process in the University-Industry relationship side and their social networks.
Conferencia en el marco de propuestas de conferencias de investigación del Departamento de Economía y Administración de Empresas y Vicerrectorado de Innovación Social y Emprendimiento
Keywords: Marketing; Administración; Service Dominant Logic, Ecosystems, Entrepreneurship, Startup